Analysis of obstacle factors in the collaborative governance of the ecological environment in the yellow river basin - Liu, Jianting; Hao, Jixiang; Su, Limin; Hua, Wenchao (Frontiers in Environmental Science, 2025)
Collaborative governance (co-governance) is a crucial pathway and essential strategy for ensuring ecological security and high-quality development in the Yellow River Basin (YRB), which faces complex ecological challenges amid unbalanced regional development. This study employs a three-layer driving chain analytical framework to systematically investigate barriers to ecological co-governance in the YRB through a tiered approach. Firstly, spatial econometric methods are utilized to analyze spatial agglomeration, network strength, and spatial spillover effects, clarifying macro-level associations and driving mechanisms of ecological collaborative governance. Subsequently, tripartite evolutionary game analysis is conducted to explore the intrinsic dynamic logic of barrier factors emerging from micro-level interactions among key actors, supplemented by core driving layer theoretical analysis to investigate obstacles in the co-governance system. The results indicate that, (1) From a spatial measurement perspective, the effectiveness of ecological governance in the YRB exhibits significant spatial correlation, agglomeration, and interaction effects, with insufficient digital governance levels and structural flaws in the green industrial sector identified as key apparent-level barriers. (2) Under stable collaborative conditions, the vertical governance system operates efficiently; parameter sensitivity analysis and model robustness tests reveal that environmental protection costs in production, environmental regulation intensity, and supervision intensity are critical and sensitive parameters, significantly influencing the speed of strategic change and convergence, with the model demonstrating strong robustness. (3) Critically, divergent governance concepts and conflicting regional interests, rooted in disparities in core governance awareness and interests, constitute the most fundamental barriers to ecological co-governance.